Sonographic assessment of lower uterine segment at term with previous caesarean section - Lahiri, Sandip; Mondal, Suresh Chandra; Pal, Sudip Ranjan (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: The present study is an attempt to evaluate the efficacy of trans abdominal sonography to measure the thickness of scarred lower uterine segment at term and to detect anatomical defect if there is any to predict the risk of scar rupture. Methods: This study assessed the usefulness of sonographic measurement of lower uterine segment thickness in 100 patients with previous Caesarean patients. Lower uterine segment thickness was compared by antenatal sonography caliper measurements and observations during caesarean section. Results: Lower uterine segment thickness measured by ultrasonography correlated well with the thickness measured by vernier calipers at Caesarean section. Sensitivity of 92.86%, specificity of 77.27%, positive predictive value of 83.87% and negative predictive value of 89.47% suggested that if the thickness of lower uterine segment was 2.6 mm or more, chances of vaginal delivery following trial of labour was high. Conclusions: Antenatal ultrasonographic assessment of lower uterine segment thickness can result a successful trial of labour in women with previous caesarean section.